The rom con - Daniels, Devon (Berkley Romance, 2023)
"After a particularly brutal breakup, Cassidy Sutton has had it with dating. So when her grandmother gives her a 1950's dating guide entitled 125 Tips to Hook a Husband, she decides to turn the retro advice into an ironic "What not to do" article for Siren, the popular online women's publication she writes for. And who better to secretly test the old-fashioned tips on than Jack Bradford, chauvinistic creator of rival men's site Brawler? She'll write an article that will entertain female readers everywhere and embarrass their sexist nemesis at the same time. Two birds, one stone. But her perfect plan soon proves to be anything but. Those vintage courtship tips Cassidy was so quick to poke fun at? They actually seem to work, calling her most closely-held beliefs into question. Even worse? Jack isn't falling for any of her tricks-and it's not long before their 'fake' relationship starts to feel like the realest one of her life. As her cat and mouse game starts to spiral out of control, Cassidy has to decide if she's playing to win, or if she's willing to lose it all for love"--